Associations between family cohesion, adaptability, and functioning of patients with bipolar disorder with clinical syndromes in Hebei, China. Issue 12 (December 2019) - Zhang, Xujing; Zhao, Mingkun; Li, Jing; Shi, Ling; Xu, Xiafei; Dai, Qian; Zhang, Yanheng; Liu, Huilan; Liu, Wei; Zhang, Xiangyun; Li, Keqing; Shi, Zhanbiao; et al.
Objective: We aimed to investigate the symptoms of inpatients with bipolar disorder (BD) in different types of families, and to explore the correlations between family coherence, family adaptability, and family functioning among inpatients with BD. Methods: Inpatients with BD in Hebei, China (n = 61; mean age = 33.85±10.54; 39 males) participated in this study. Participants' symptoms were evaluated using the Bech–Rafaelsen Mania Scale (BRMS) and Hamilton Depression Rating Scale (HDRS) at weeks 1, 4, and 8 after their admission to the hospital. Participants' family type was assessed using the Family Adaptability and Cohesion Scale II–Chinese Version. Family functioning was assessed using Family Assessment Device. Results: Participants were classified into three family types: balanced (n = 13), mid-range (n = 28), and extreme (n = 20). BRMS scores improved over time in patients from all three family types. Improvement was slightly better with the balanced than the extreme family type. HDRS scores showed an improving trend over time, although this was not significant. Family coherence, adaptability, and functioning were mutually correlated. Conclusion: The family system and family functioning are important factors that clinicians should keep in mind when treating people with BD.